Resolution All-Russian Scientific and Practical Conference with International Participation «Health Care-Associated Infections - an interdisciplinary approach to prevention» with the meeting of the Profile Commission on Epidemiology of the Ministry of Healthcare of Russia (Эпидемиология и вакцинопрофилактика)
April 24-25, 2019, Yekaterinburg